Perlindungan Hukum Terhadap Pemenang Lelang Benda Bergerak Non Eksekusi Sukarela di Balai Lelang Swasta - Saputra, Dimas Almeida; Arifin, Zaenal; Sudarmanto, Kukuh; Sukrisno, Wijayono Hadi (Journal Juridisch, 2024)
This research aims to analyze the process of implementing a voluntary non-execution movable object auction at PT JBA Indonesia Semarang City Branch. As well as to analyze legal protection for winners of non-voluntary execution movable object auctions at PT JBA Indonesia Semarang City Branch. The urgency of this research is so that auction winners are not deceived by the condition of movable objects when they are declared to have won the auction. And so that the auction winner gets legal protection and understands the legal standing at the time of the auction. This writing is empirical juridical research with a statutory approach and a case approach. The research specifications used in this research are analytical descriptive. The data collection method used by the author is by examining primary data obtained through interviews with employees and assistants to the leadership of the private auction house PT JBA Indonesia, Semarang City Branch, which was conducted directly at the PT JBA Indonesia Semarang City Branch office and secondary data obtained from materials. References. The results of the research explain that the auction implementation at the private auction center PT JBA Indonesia uses a voluntary non-execution auction type, then the auction implementation is also divided into several categories, namely pre-auction, during the auction, and post-auction. There are several categories of legal protection for winners of auctions for non-voluntary movable objects, namely disclosure of information about auction winners, private auction houses daring to take responsibility for errors in auction implementation and special complaints regarding auction implementation.